The cost-effectiveness of antenatal and postnatal education and support interventions for women aimed at promoting breastfeeding in the UK - Ifigeneia Mavranezouli; Jo Varley-Campbell; Sarah Stockton; Jennifer Francis; Clare Macdonald; Sunita Sharma; Peter Fleming; Elizabeth Punter; Charlotte Barry; Maija Kallioinen; Nina Khazaezadeh; David Jewell (BMC, 2022)
Abstract Background Breastfeeding is associated with health benefits to mothers and babies and cost-savings to the health service. Breastfeeding rates in the UK are low for various reasons including cultural barriers, inadequate support to initiate and sustain breastfeeding, lack of information, or choice not to breastfeed. Education and support interventions have been developed aiming at promoting breastfeeding rates. The objective of this study was to assess the cost-effectiveness of such interventions for women, initiated antenatally or in the first 8 weeks postnatally, aiming at improving breastfeeding rates, in the UK. Methods A decision-analytic model was constructed to compare costs and quality-adjusted life-years (QALYs) of a breastfeeding intervention from the perspective of health and personal social services in England. Data on intervention effectiveness and the benefits of breastfeeding were derived from systematic reviews. Other model input parameters were obtained from published sources, supplemented by expert opinion. Results The incremental cost-effectiveness ratio (ICER) of the modelled intervention added on standard care versus standard care was £51,946/QALY, suggesting that the intervention is not cost-effective under National Institute for Health and Care Excellence (NICE) criteria in England. Sensitivity analysis suggested that the cost-effectiveness of the intervention improved as its effectiveness increased and intervention cost decreased. At the base-case effect (increase in breastfeeding rates 16-26 weeks after birth by 19%), the intervention was cost-effective (<£20,000/QALY) if its cost per woman receiving the intervention became ≈£40-£45. At the base-case cost (£84), the intervention was cost-effective if it increased breastfeeding rates by at least 35-40%. Conclusions Available breastfeeding interventions do not appear to be cost-effective under NICE criteria in England. Future breastfeeding interventions need to have higher effectiveness or lower cost compared with currently available interventions in order to become cost-effective. Public health and other societal interventions that protect, promote and support breastfeeding may be key in improving breastfeeding rates in the UK.